Same time next Christmas - Alexander, Victoria (NYLA, 2015)
My friends have always considered me the most proper among us. But no one was more surprised than I, Portia, Lady Redwell, when I decided to flee the matchmaking efforts of my family to spend Christmas in an enchanting villa on the coast of Italy. My admittedly impulsive plans were immediately complicated by the presence of a certain gentleman, Mr. Fletcher Jamison, who insisted he had a claim on the villa. It was only in the true spirit of Christmas that I agreed to share the villa with him. His charm, his blue eyes as dark as the December seas, and the laugh that oddly seemed to fill my soul were not considerations. That I returned again for Christmas is due entirely to the charm of the villa, and nothing to do with the fact that he too would be there. My friend Veronica has often said those least likely to bend are most likely to snap. It appears I have snapped." -- Back cover